BANKING FINANCIAL PERFORMANCE USING THE CAMEL METHOD AT BCA AND BRI BANKS REGISTERED AT LQ 45 - Fitriani, Fitriani (Journal of Innovation Research and Knowledge, 2023)
This study aims to determine the financial performance of banks using the CAMEL method for BCA and BRI Registered at LQ 45. The data analysis method used in this research is descriptive qualitative. The data used in this study is data sourced from income statements, balance sheets and notes to other financial reports for the 2019-2021 period. The variable in this study is the independent variable while the variable is financial performance. The assessment of financial performance is carried out using the CAMEL method. The financial performance results using the CAMEL method at Bank BCA and BRI in the 2019-2021 period are considered Healthy because the CAMEL calculation results are in the 81% - 100% classification. For CAMEL yields at Bank BCA were 90.67%, 90.83% and 90.98% while for CAMEL yields at Bank BRI were 96.89%, 92.84% and 97.46%.